Criticizing in English and Arabic Tweets: A Pragmatic Contrastive Study - Adai AlMamoory, Salih Mahdi; Atshan Al-Fayadh, Sameerah (International Journal of Psychosocial Rehabilitation, 2021)
Twitter is a social networking platform. It enables people to know what is happening and what people are talking about right now. This paper scrutinizes criticizing in English and Arabic tweets. The present study fulfills a pragmatic contrastive study of English and Arabic tweets represented by Mr. Bean and Al-Zaeem’s tweets. The following questions summarize the problem of the study: 1. What are the strategies used in English and Arabic tweets? 2. How does the structure of tweets differ from one actor’s use to another? The study aims to achieve the following: 1. Finding out the different strategies used by the two actors when criticizing. 2. Identifying the different structures used in English and Arabic tweets. It is hypothesized that: 1. Direct criticism is highly avoided in English and Arabic for certain cultural reasons. 2. Indirect criticism is highly employed in English tweets. 3: Direct criticism is highly employed in Arabic tweets. 4 The two tweets are different in their structures.